2018
DOI: 10.1016/j.socscimed.2018.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the conceptualisation of risk in the context of community dementia care

Abstract: Risk has become a ubiquitous presence in modern society. For individuals diagnosed with dementia this preoccupation with risk can affect their day-to-day life in many ways. Maintaining autonomy while balancing risks is a continual struggle not only for those living with the disease, but also their carers, family and health professionals. To understand how these different groups of individuals conceptualise the issue of risk for those living with dementia, 83 semi-structured interviews were conducted with peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 19 publications
1
25
0
2
Order By: Relevance
“…In addition to how such situations affect the nuclear family (both the caregiver and other members), this research has identified three further variables which influence the adjustment process of family caregivers of people suffering from Parkinson's disease or dementia: employment status, income, and place of residence. is result is in line with studies such as that of Dickins et al [17] on the risk of dementia care. According to the authors, the personal context (cultural and professional) must be taken into account to identify and understand different perspectives and discourses on a social reality such as care.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition to how such situations affect the nuclear family (both the caregiver and other members), this research has identified three further variables which influence the adjustment process of family caregivers of people suffering from Parkinson's disease or dementia: employment status, income, and place of residence. is result is in line with studies such as that of Dickins et al [17] on the risk of dementia care. According to the authors, the personal context (cultural and professional) must be taken into account to identify and understand different perspectives and discourses on a social reality such as care.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, according to the World Health Organization [11]; the measures taken to care for people with neurodegenerative diseases have been insufficient despite this expenditure. For Australia, Dickins et al [17] reported that 75% of people with dementia remain at home. In other cases, it has been estimated that between 60% and 80% of home care is informal [18] and that those with the disease live with their caregivers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, first and foremost professionals felt it necessary to understand and address the carer's expectations of the person living with dementia if these were unduly influential: (Quinn et al, 2013, p. 597) Carers themselves sometimes felt like they had failed if paid care was taken on and some saw professionals as interfering (Bowes & Wilkinson, 2003;Dickins et al, 2018;Gilmour et al, 2003;Maidment et al, 2017;Stephan et al, 2018). From the perspective of the carers, taking over some of their relatives' decisions was seen as part of their 'duty': The role of health care professionals was complex, as for example some GPs felt that their support for the person living with dementia and their family could take on a counselling role (Foley et al, 2017), but there were also comments that disagreed with the idea that there was a therapeutic expectation of the health care professional role (Martin et al, 2013).…”
Section: Expectations Of Care and Of The Role In The Triadmentioning
confidence: 99%
“…Results indicate a focus on the priorities of caregivers rather than people with dementia. People with dementia identify daily activities and socialising as their priority (46). Focussing on activities which increase participation can increase wellbeing, and reduce anxiety related behaviour such as wandering (22).…”
Section: Discussionmentioning
confidence: 99%